Decree of the Minister of Finance No. 172 of the year 2015Amending Some Provisions of the Executive Regulations of the Income Tax Law Promulgated by the Minister of Finance Decree No. 991 of the year 2005 - Egypt (2025)
Ministry of finance decree no. 172 of the year 2015 on amending Some Provisions of the executive regulations of the income tax Promulgated by the minister of finance decree no. 991 of the year 2005 وزارة المالية قرار رقم 172 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادر بقرار وزير المالية رقم 991 لسنة 2005